Prevalence of hepatitis B and C and sensibility of a selective screening questionnaire in patients receiving chemotherapy for solid tumors. Issue 1 (December 2015) - Brasseur, Mathilde; Heurgué-Berlot, Alexandra; Barbe, Coralie; Brami, Cloé; Rey, Jean-Baptiste; Vella-Boucaud, Juliette; Dabouz, Fadia; Deslée, Gaëtan; Grange, Florent; Volet, Julien; Bouché, Olivier
Abstract Background Reactivation of hepatitis B or C virus can occur in patients undergoing chemotherapy. Recommendations for selective or systematic hepatitis B virus testing prior chemotherapy for solid tumors differ. The primary aim was to determine the seroprevalence of hepatitis B or C in a low endemic country. The second objective was to assess the relevance of a questionnaire on hepatitis B/C risk factors to consider a selective screening. Methods Patients were prospectively tested for hepatitis B/C markers. HBs antigen positive patients and isolated anti-HBc positive patients with detectable viral load received antiviral preventive treatment. Patients or physicians completed the questionnaire on infection risk factors. Results Among the 450 patients included, 388 were tested for all serological markers and had gastrointestinal (63.7 %), lung (31.2 %) and skin (4.6 %) cancers. The prevalence of subjects exposed to hepatitis B virus was 8.5 % (33/388). One patient tested positive for HBs antigen and received preventive treatment. Prevalence of subjects exposed to hepatitis C was 1.3 % (5/388). The questionnaire sensitivity was 45.5 %, 100 % and 50 % for detecting carriers of hepatitis B, C and one or the other, respectively. Conclusions Seroprevalence of hepatitis B was low. Selective screening with the questionnaire was insufficiently sensitive. Systematic screening with serological tests prior to chemotherapy in patients with solid tumors is therefore relevant.